VARIASI SOSIOLEK DAN DIALEK BAHASA JAWA PADA MASYARAKAT TULANGAN - Dewi Farah Arisa Putri; Titik Indarti; Resdianto Permata Raharjo (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Dialects are variously differentiated by different language origins and different social classes of speakers, hence, geographical and social either dialects or socioleone. The study aims to find out how a variety of socialites might be in tulans and expose the Javanese dialects to tulans using a qualitative approach with descriptive methods. The source of the data in this research is society itself. Data collection techniques drawn from observation, observation, and conversation are contagious. Studies have shown that there are variations in socialens and dialects of Javanese in tulangan communities. Keywords: Sociolek, dialect, Javanese